Visual dysfunction, but not retinal thinning, following anti-NMDA receptor encephalitis - Brandt, Alexander U. (Neurol Neuroimmunol Neuroinflamm, 2016)
OBJECTIVE: To assess structural and functional changes in the afferent visual system following anti-NMDA receptor (NMDAR) encephalitis. METHODS: In this cross-sectional study including 31 patients after acute NMDAR encephalitis and matched healthy controls, visual function was assessed as high-contrast visual acuity using Early Treatment Diabetic Retinopathy Study charts and low-contrast sensitivity using Functional Acuity Contrast Test. Retinal changes were measured using optical coherence tomography with assessment of peripapillary retinal nerve fiber layer (pRNFL) and macular intraretinal layer thicknesses. Residual clinical impairment was described using the modified Rankin Scale. RESULTS: High-contrast (logMAR 0.02 ± 0.14 vs −0.09 ± 0.14, p < 0.001) and low-contrast (area under the curve 1.89 ± 0.21 vs 2.00 ± 0.26, p = 0.039) visual acuity were reduced in patients in comparison to healthy controls. More severely affected patients performed worse in visual acuity testing than patients with good recovery (logMAR −0.02 ± 0.11 vs 0.08 ± 0.17, p = 0.030). In contrast, patients did not differ from matched healthy controls in pRNFL or in thickness of intraretinal layers, including the ganglion cell complex, the inner nuclear layer, the outer nuclear and plexiform layers, and the photoreceptor layer. CONCLUSIONS: After acute NMDAR encephalitis, patients have mild visual dysfunction in comparison to matched healthy controls, while retinal structure appears unaltered. These observations could point to an impairment of anterior or posterior visual pathway NMDAR function that is similar to dysfunction of NMDAR in cerebral cortex and subcortical structures. Alternatively, residual cognitive impairment might reduce visual function.